2015
DOI: 10.1111/jnc.13377
|View full text |Cite
|
Sign up to set email alerts
|

Influence of caffeine on 3,4‐methylenedioxymethamphetamine‐induced dopaminergic neuron degeneration and neuroinflammation is age‐dependent

Abstract: Previous studies have demonstrated that caffeine administration to adult mice potentiates glial activation induced by 3,4-methylenedioxymethamphetamine (MDMA). As neuroinflammatory response seems to correlate with neurodegeneration, and the young brain is particularly vulnerable to neurotoxicity, we evaluated dopamine neuron degeneration and glial activation in the caudate-putamen (CPu) and substantia nigra pars compacta (SNc) of adolescent and adult mice. Mice were treated with MDMA (4 9 20 mg/kg), alone or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 82 publications
(201 reference statements)
3
24
1
Order By: Relevance
“…In contrast, chronic low doses of caffeine exerted anti-inflammatory effects and prevented MDMA-induced neuroinflammatory reaction (Ruiz-Medina et al 2013 ). Study of Frau et al ( 2016 ) showed that caffeine potentiated MDMA-induced DA neuron degeneration and neuroinflammation in adolescent mice. Vanattou-Saïfoudine et al ( 2012 ) proposed that caffeine exacerbated adverse reactions induced by various psychostimulants, such as hyperthermia, tachycardia, and increased mortality as the result of increased DA release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, chronic low doses of caffeine exerted anti-inflammatory effects and prevented MDMA-induced neuroinflammatory reaction (Ruiz-Medina et al 2013 ). Study of Frau et al ( 2016 ) showed that caffeine potentiated MDMA-induced DA neuron degeneration and neuroinflammation in adolescent mice. Vanattou-Saïfoudine et al ( 2012 ) proposed that caffeine exacerbated adverse reactions induced by various psychostimulants, such as hyperthermia, tachycardia, and increased mortality as the result of increased DA release.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier results indicated that exacerbation of MDMA effect on DA and 5-HT release by caffeine in mice was mediated via adenosine A1 and A2A receptors (Górska and Gołembiowska 2015 ). The results of Khairnar et al ( 2010 ) and Frau et al ( 2016 ) demonstrated that neuroinflammatory response induced by MDMA in adult C57BL/6J mice and mice treated in adolescence with MDMA was potentiated by caffeine. The abovementioned data suggest that caffeine increases MDMA-related neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The density of immunoreacted fibers was determined quantitatively using the ImageJ program (U.S. National Institutes of Health, USA). No significant differences in the density of immunoreacted fibers were seen between the three sections, thus values from different levels were averaged (Frau et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, no reports are available showing cocaine treatment increasing reactive astrogliosis in the dorsal striatum. Moreover, other conditions where other psychostimulants were co-administered with caffeine reported that caffeine can potentiate astrogliosis in different SNC areas (Khairnar et al 2010; Frau et al 2015). We have found increased GFAP-positive astrocytes in the dorsal striatum after chronic psychostimulant treatment and after 7 days of withdrawal.…”
Section: Resultsmentioning
confidence: 97%
“…Even if many studies are not available reporting cocaine effects on astrocyte reactivity, GFAP has been previously demonstrated to be responsive to cocaine administration (Freeman et al 2010; Blanco-Calvo et al 2014). In addition, it was previously shown that caffeine enhanced astroglia and microglia reactivity induced by MDMA in the mouse striatum (Khairnar et al 2010) and that caffeine can potentiate MDMA-induced neurotoxicity (Frau et al 2015). Moreover, caffeine potentiated the neurotoxic effects of methamphetamine (Sinchai et al 2011).…”
Section: Discussionmentioning
confidence: 99%